2021
DOI: 10.1101/2021.02.03.21251088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comparison of Methylprednisolone and Dexamethasone in Intensive Care Patients with COVID-19

Abstract: OBJECTIVES: This study retrospectively compares the effectiveness of methylprednisolone to dexamethasone in patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 or COVID-19) requiring ICU care. DESIGN: This is an institutional review board approved cohort study in patients with COVID-19 requiring intensive care unit admission. Patients admitted and requiring oxygen supplementation were treated with either methylprednisolone or dexamethasone. SETTING: This study takes place in the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 13 publications
(22 reference statements)
1
41
0
4
Order By: Relevance
“…In this study, all-cause mortalities in the usual care, methylprednisolone, and dexamethasone groups were 41.3%, 16.4% and 26.5% at 50 days ( P < 0.01) respectively. 45 It was found that in patients requiring mechanical ventilation, mortality was 42% lower in the methylprednisolone group than in the dexamethasone group (hazard ratio 0.48, 95% CI: 0.235–0.956, P = 0.0385).…”
Section: Target Therapeutic Agents Rounding Up the Immunopathologymentioning
confidence: 97%
See 1 more Smart Citation
“…In this study, all-cause mortalities in the usual care, methylprednisolone, and dexamethasone groups were 41.3%, 16.4% and 26.5% at 50 days ( P < 0.01) respectively. 45 It was found that in patients requiring mechanical ventilation, mortality was 42% lower in the methylprednisolone group than in the dexamethasone group (hazard ratio 0.48, 95% CI: 0.235–0.956, P = 0.0385).…”
Section: Target Therapeutic Agents Rounding Up the Immunopathologymentioning
confidence: 97%
“…19 to Jun. 8, 2020), n=6425 6 mg (oral or intravenous once daily) 28-day mortality Dexamethasone: 482 of 2104 (22.9%) vs Control: 1110 of 4321 (25.7%) (p<0.001) Methylprednisolone Dexamethasone Ko JJ et al, 2021, 45 USA Cohort study (Mar. 1 to Jul.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, clinical pharmacology properties of corticosteroids have been ignored, which could lead to misleading data. [10][11][12] For example, Ranjbar et al 10 carried out a prospective triple-blinded RCT to compare the effectiveness of methylprednisolone (2 mg/kg/d and tapered to half dosage every 5 days [intervention group]) with the RECOVERY trial dose of dexamethasone (6 mg/d for 10 days [control group]) in 86 hospitalized adult patients with COVID-19. They concluded that methylprednisolone (2 mg/kg/d) is superior to dexamethasone (6 mg/d) in decreasing need for mechanical ventilation (18.2% vs 38.1%; P = .040), hospital length of stay (7.43 ± 3.64 vs 10.52 ± 5.47; P = .015), and improving clinical status at days 5 (4.02 vs 5.21; P = .002) and 10 (2.90 vs 4.71; P = .001).…”
mentioning
confidence: 99%
“…It is important to mention that the dose of corticosteroid in the methylprednisolone group was higher in Ko and colleagues' study than the National Institutes of Health panel recommendation; however, according to the previous evidence on the potential beneficial efficacy of high doses of corticosteroids in the treatment of classic ARDS, the evaluation effects of 1 mg/kg of methylprednisolone seems to be rational in patients with severe COVID-19. 9,11,14,15 Pinzón et al, 12 in an ambispective cohort study in 216 patients with severe COVID-19 pneumonia showed that high-dose methylprednisolone (250-500 mg/d for 3 days) followed by oral prednisone (50 mg daily) for 14 days leads to statistically significant lower recovery time (P < .0001), C-reactive protein (P < .0001), d-dimer (P = .04), and lactate dehydrogenase (P = .01) compared with dexamethasone (6 mg/d for 10 days). Moreover, in Pinzón and colleagues' study, the rate of mortality and intensive care unit admission were lower in the methylprednisolone group compared with the dexamethasone group (4.8% vs 14.4%; 9.5% vs 17.1%).…”
mentioning
confidence: 99%
See 1 more Smart Citation